City-campus, or Educational Space of the City. Methodological Construct - S. A. Smirnov (Высшее образование в России)
The article considers the city from the point of view of its educational potential and in the categories of educational space, approaching the main cultural and historical forms of the city as educational institutions. With this review, at least three focus points are retained: 1) Consideration of the city space and its infrastructure as an educational space and educational infrastructure that are not reducible to usual school and university (the latter should also be culturally and historically distributed, showing their basic etymons and missions); 2) Consideration of education as an institution of educational and, more broadly, anthropological practices of the development and formation of a person, and not as a disciplinary institution and matrix; 3) Consideration of the repertoire of anthropological practices development as a practice unfolding in urban space. It is shown that these three foci act as mirrors directed at each other, mirroring and showing each other mutual potential and mutual scarcity, the need for each other. The actual wealth (thesaurus) of the urban space depends on the density, frequency and variety of connections between these areas. Next, we look at specific cultural and historical forms, such as the Temple, School, Museum, University, etc., which constitute the basic infrastructure nodes of the city space itself. These cultural institutions are considered not so much from the point of view of their internal tasks, but from the position of their place in the city, in the urban space, with regard to their place and role as special educational nodes-institutions in this space. Further, the urban space is considered in the categories of the campus city, in which this space is linked by different anthropological practices repertoires.